Problematika Keluarga terhadap Nafkah Suami akibat Pandemi Covid 19 - Dewi Intan Fitriani, Alivia (HOKI : Journal of Islamic Family Law, 2023)
A harmonious family is formed by itself, namely from those who build the family, not from ancestral inheritance. A harmonious family is formed thanks to the efforts of family members who communicate and interact with each other in the family environment. Researchers used qualitative research methods with descriptive research type. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people or observed behavior. The research results show that the outbreak of Covid-19 caused many heads of families to lose their jobs, they only worked as motorbike taxi drivers and workers selling corn rice. So many family needs cannot be met because the income provided by the husband is only enough for food, and that is why disputes often occur in the family.